15.7k views
0 votes
What is the solution to : 3(1/2 m - 3) =45

User Gnud
by
5.3k points

2 Answers

7 votes

Answer:

m = 36

Explanation:

Step 1:

3 ( 1/2m -3 ) = 45

Step 2:

3/2m - 9 = 45

Step 3:

3/2m = 54

Step 4:

54 ÷ 3/2

Step 5:

54/1 × 2/3

Answer:

m = 36

Hope This Helps :)

User Jem Tucker
by
4.9k points
3 votes

Answer:


m=36

Explanation:

We can solve for this equation by isolating
m on one side. To do this, we can "reverse" the equation.


3((1)/(2)m - 3) = 45

Let's divide both sides by 3.


3((1)/(2)m-3)/3 = 45/3\\\\(1)/(2)m - 3 = 15

Add 3 to both sides:


(1)/(2)m - 3 + 3 = 15 + 3\\\\(1)/(2)m = 18

Multiply both sides by two (since
(1)/(2)\cdot2=1)


(1)/(2)m \cdot 2 = 18 \cdot 2\\\\m = 36

Hope this helped!

User Andrei Dvoynos
by
5.3k points